Effect of different sucrose and nitrogen salt levels in the medium and temperature on in vitro propagation of Helleborus niger L. - Eleonora Anna Gabryszewska (Acta Agrobotanica, 2015)
Helleborus niger L. is a rhizomatous, herbaceous perennial with overwintering, divided, basal leaves. The objective of the study was to investigate the influence of different levels of sucrose (10, 20, 30, 40, 50, 60, 70, and 80 g l−1) and nitrogen salts (25%, 50%, and 100% according to MS medium) as well as temperature (15°C, 20°C) on in vitro multiplication and rooting and ex vitro acclimatization of H. niger. The growth and multiplication of axillary shoots were performed on modified MS medium supplemented with various growth regulators (2iP, BAP and kinetin – each at a concentration of 1.0 mg l−1, GA3 2.5 mg l−1). For the induction of roots, the medium was supplemented with IBA 1 mg l−1 and NAA 0.1 mg l−1. Rooted plants were transplanted in a peat–perlite substrate (4:1) in a heated greenhouse for ex vitro acclimatization. The multiplication rate of H. niger shoots, in vitro rooting, and ex vitro acclimatization were strongly dependent on the sucrose/nitrogen salt relationship in the medium. The highest multiplication rate of axillary shoots (3.7) was found at a temperature of 15°C or 20°C, on the medium with cytokinins and GA3 supplemented with sucrose 20–30 g l−1 and nitrogen salts at 50%. Sucrose at a concentration of 50 g l−1 strongly stimulated the number of roots per microplant (5.8–6.0) on the media with a reduced level of nitrogen salts (25% and 50%) when the temperatures were 20°C and 15°C, respectively. The plants rooted on the media with a high sucrose/nitrogen salt ratio showed acclimatization rates which ranged from 82% to 100%. Morphological observation of plantlets revealed obvious differences in leaf shape and size and the architecture of the root system as well as differences in the developmental stages of shoots grown on media with different sucrose and nitrogen salt concentrations.